2020
DOI: 10.3390/app10093326
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Water in the Effect of Weak Combined Magnetic Fields on Production of Reactive Oxygen Species (ROS) by Neutrophils

Abstract: Various models have been used to demonstrate the pronounced effects of the microwave frequency range electromagnetic fields, as well as weak and very weak combined collinear magnetic fields (CMF) with static and variable components in the order of micro- and nano-tesla. One of such models, previously shown to be sensitive to variations in the parameters of applied magnetic fields, is the neutrophil respiratory burst. Using luminol-enhanced cell chemiluminescence assay, we studied the effects of the CMF exerted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 24 publications
1
18
0
Order By: Relevance
“…A recent finding is important in understanding the mechanisms of activity for extremely diluted solutions and how they are influenced by physical factors. It has been discovered that the preparation of effective extremely diluted solutions is impossible under hypomagnetic conditions [4]. Many works have been devoted to identifying various nanoscale objects in such dilutions [1,2,[5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent finding is important in understanding the mechanisms of activity for extremely diluted solutions and how they are influenced by physical factors. It has been discovered that the preparation of effective extremely diluted solutions is impossible under hypomagnetic conditions [4]. Many works have been devoted to identifying various nanoscale objects in such dilutions [1,2,[5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…It is known that water is able to change its functional characteristics under the influence of weak and superweak magnetic fields [4]. In order to minimise the effect of external undesirable physical influences on the studied samples, the same number of saturated lactose samples and control samples were tested on each day of the experiment; in general, each type of experimental sample was tested in 6 independent repeats.…”
mentioning
confidence: 99%
“…At the same time, performing serial dilutions of magnetically pre-treated water, but at a near-zero magnetic field (inside a permalloy shielding chamber with a residual field of ~10 nT) led to a complete loss of the ability to activate neutrophils. The stimulating properties were also demonstrated for diluted water that was pre-incubated in an artificial CMF (comparable with the GMF) generated inside the magnetically shielded chamber [11]. All these results indicate the critical role of the magnetic environment in the generation and retention of this biological activity in water.…”
Section: Of 15mentioning
confidence: 59%
“…In order to conduct such studies, it was necessary to find an experimental model that clearly relates the change in biological activity under the influence of water subjected to a physical exposure (for example, after incubation in a magnetic field). We have previously shown that combined magnetic fields (CMF) with a 60 µT static component and a collinear variable component with an amplitude of 100 nT at a frequency of 12.6 Hz at one hour exposure stimulate the chemiluminescent response of neutrophils to the administration of the respiratory burst activator, the bacterial peptide N-formyl-Met-Leu-Phe (fMLF) [11].…”
Section: Introductionmentioning
confidence: 99%
“…One could also mention the developing concept of the involvement of metastable states of water and proton exchange in nonspecific magnetic effects. In recent experiments, data were obtained on various spin and structural rearrangements of water in EMF [ 48 , 49 , 50 , 51 , 52 , 53 ].…”
Section: Plausible Molecular Mechanisms Of Nonspecific Mf Effectsmentioning
confidence: 99%